Care for health – organizational perspective - Lubrańska, Anna (Contemporary problems of physical and health culture, 2022)
Human health is an issue of interest to individuals and various institutions. It is also the subject of research and implementation of practical applications among representatives of organization and management sciences. One of the more and more popular ideas today is age management – a solution that uses the value of generational diversity to comprehensively take care of employee resources. An important area of implementing this idea is concern for the health and safety of the participants of the organization.The study presents the results of research illustrating the assessment of selected practices, aimed at the protection and promotion of employeesʼ health. 757 employees aged 20–78 participated in the study. The study used the Job Satisfaction Scale, the Organizational Commitment Scale and a proprietary questionnaire, taking into account organizational practices in the field of health protection and promotion. Frequency distributions, Spearmanʼs rank correlation analysis, and crosstabs with chi-square tests were counted. The respondents rated the organizationʼs activity in the area of care for the safety of working conditions and risk control the highest. An important determinant of organizational activities is the type of organizational climate. Significant positive relationships between the frequency of the companyʼs activities for the protection of employees’ health and satisfaction with work and organizational commitment were revealed.